A Review and Comprehensive Analysis of the Performance of University – Construction Industry Collaboration - Ziad Al-Gasim; Aslan Amat Senin; Mohd Effandi bin Yusoff (Civil Engineering Journal, 2021)
University–construction industry collaboration (UIC) has become an essential part of driving innovation and fostering construction industry growth. Measuring the performance of such collaboration is an emergent field of study that is scattered through the current literature. This study aims to identify the UIC performance indicators advocated by the top-cited references, and map UIC performance indicators in the context of the state of Qatar. The present research evaluated the literature related to measuring the performance of UIC, considering publications in selected scientific databases over the period of 2004 – 2020. The publications were obtained through a search of the Science Direct, Emerald Insight, Scopus, Web of Science, Springer Link, SAGE, Research Gate, and Taylor & Francis Online databases. Keywords used in searching for publications included university, construction industry, business, cooperation, collaboration, relation, performance, and measurement. The findings were discussed and confirmed in the context of Qatar’s education and innovation ecosystem through semi-structured interviews with two renowned scholars who are involved in UIC. The study revealed that both universities and the construction industry are increasingly focused on measuring the performance of collaboration through specific performance indicators. The results show that both universities and the construction industry share some interests when it comes to four key performance indicators. These performance indicators are (1) the number of registered patents, (2) the number of patent applications, (3) the number of innovations (process/marketing/product/organisational), and (4) the number of publications. This study contributes to a general understanding of measuring UIC performance and defining trends in this research field. It also highlights research limitations and provides an arena for future research in the field. Doi: 10.28991/cej-2021-03091688 Full Text: PDF